Seasonal variation in arsenic concentration and hydrogeochemical dynamics in groundwater at Van Phuc, Thanh Tri, Hanoi - Vu, Thi Duyen; Nguyen, Thanh Dam; Pham, Thi Kim Trang; Pham, Hung Viet; Berg, Michael (Vietnam Journal of Science and Technology, 2025)
Arsenic contamination in groundwater represents a significant public health threat to millions of people globally, particularly within the Red River Delta region of Vietnam. This study aims to assess the seasonal fluctuations in arsenic concentration and the underlying hydrogeochemical dynamics of groundwater at Van Phuc, Thanh Tri, Hanoi. Groundwater samples were collected from 17 wells, with depths ranging from 25 to 54 meters, during three distinct seasons: pre-monsoon, monsoon, and post-monsoon. Physicochemical analysis indicates that groundwater quality is predominantly influenced by local biogeochemical processes within the aquifer, coupled with year-round river recharge. In contrast, anthropogenic impacts, such as irrigation and wastewater discharge, appear to exert minimal influence. Arsenic concentrations exhibited a slight increase, from 132 µg/L in the pre-monsoon to 141 µg/L in the monsoon and reaching 145 µg/L in the post-monsoon season.  Notably, seasonal fluctuations were more pronounced in shallow groundwater (<30 meters), with a progressive reduction in variability as the distance from the Red River increased. These fluctuations are driven by arsenic mobility under varying redox conditions and the local geohydrochemical processes. Additionally, high phosphate concentrations were found to enhance the arsenic variation in groundwater. Health risk assessments revealed a high hazard index (HI > 1) and unacceptable carcinogenic risk (ILCR > 10⁻⁴) in most wells, underscoring the need for mitigation measures. This study provides insights into the seasonal hydrogeochemical processes governing arsenic contamination, with implications for groundwater management in affected regions. Further research is needed to refine mitigation approaches and reduce exposure risks.